‎ Sudan’s accession to the World Trade Organization and its impact on the proceeds of tax and customs revenues (Field study) - Khair Elseed, Abdelsalam Awad (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to recognize the extent of Sudan government interest with increasing its public revenues through its quest to join world trade organization, to study the relationship between join world trade organization and increasing the tax and customs revenues for the state. The study adopted descriptive approach to analyze study’s data and hypotheses testing. The study found several results, among which is that, join world trade organization impacts on tax and customs revenues through tax facilities and customs’ reductions which provided by joining the organization, implementing principles of cancels customs tariff according to world trade organization requirements impacts public revenues of the state. The study recommended many recommendations, among which is that, Sudanese government should do more efforts towards complete obligation of implementing World trade organization’s guidance, increasing custom’s control procedures to ensure correct implementation for world trade organization’s articles that concern customs performance.